Long-term changes in precipitation and streamflow in five major Peninsular Malaysia river basins - Zamil, Mahmud Shafayet; Zulkafli, Zed; Ab Razak, Mohd Shahrizal; Tan, Mou Leong; Yusop, Zulkifli (John Wiley and Sons, 2025)
Despite increasing evidence of the hydrological impacts of climate change, gaps persist in our understanding of the intricate precipitation and streamflow dynamics. Our research investigates the temporal and spatial relationships between precipitation and streamflow for five Malaysian river basins in a 50-year period (1973–2022). Our analysis shows shifts in precipitation time series from 1992 onward and streamflow time series from 1983 onward. The Peninsula's western region experienced significant increases in the annual mean daily precipitation, while positive trends in annual maximum precipitation were identified in only select stations in 3 out of 5 basins. Seasonally, the Perak River Basin demonstrated an evident increase in precipitation during the North-East Monsoon (NEM) that was not reflected in any significant trends in streamflow. Similarly, the Pahang River Basin exhibited positive precipitation trends during both the NEM and Southwest Monsoon (SWM), yet no significant trends were observed in streamflow categories. The Klang River Basin indicated positive precipitation trends in the NEM and SWM that were also reflected in increasing trends in streamflow. Kelantan and Johor River Basins, on the other hand, showed negative trends in streamflow. The trends and shifts in precipitation and streamflow might be ascribed to multiple factors, including regional climate variability, dam operation, mining and land use changes. These findings are of considerable significance in enhancing our understanding of the hydrometeorological dynamics in the region.